EFEKTIVITAS TEKNIK DEEP BREATHING RELAXATION TERHADAP DISMINORE PADA MAHASISWI KEBIDANAN STIKES AL-MAARIF BATURAJA - Agustia, Nency; Astriana, Willy (STIKES Abdurahman. Pusat Informasi dan Manajemen, 2024)
ABSTRACT Dysmenorrhea is pain during menstruation which makes women uncomfortable because make women experienced unable activities which can disrupt their work for several hours or several days. On survey conducted by researchers using numerical pain scale on 22 female students who experienced dysmenorrhea, 18 female students had to be absent on the first day of menstruation or take pain medication because the dysmenorrhea was very severe and they were unable to participate in the learning process. One effective method to overcome this is the deep breathing relaxation technique. Pain scale measurements are carried out using a numerical scale of 1-10. The aim of this study was to determine the difference in the intensity of dysmenorrhea before and after the deep breathing relaxation technique was carried out on Midwifery Students at STIKes Al-Ma'arif Baturaja. This research method is pre-experiment which is one group pretest-posttest. With a sample size of 58 people using the accidental sampling method and data analysis using the dependent t-test. The research was conducted from October to December 2023. The instrument in this study was an observation sheet which included pain levels on a numerical scale of 1-10. From the results of the t-dependent test, it was found that the pain intensity before the deep breathing relaxation technique was carried out, the average value was 5.24, the standard deviation was 1.204, and after the intervention, the average value was 2.62, the standard deviation was 1.254, and the average difference in the pain scale before and after intervention 0.741 with a standard deviation of 0.133. From the results of the t-dependent statistical test, it can be concluded that there is a significant effect of the deep breathing relaxation technique on dysmenorrhea with a P value = 0.000. It is recommended that women who experience dysmenorrhea apply deep breathing relaxation techniques to reduce pain.